Oxidative Stress & C – Reactive Protein In Patients With Arthritis - Thanoon, Imad A.; Tawfik, Nahla O.; Hussin, Farhad N. (Journal of the Faculty of Medicine Baghdad, 2007)
Back ground: Oxidative damage has been suggested to play a key role in accelerating inflammation and to be involved in the pathogenesis of rheumatoid arthritis (RA) and osteoarthritis (OA). Many studies had shown that those patients have low antioxidants level and are at risk of increased oxidative stress. Objective: This study was designed to examine the levels of serum Total Antioxidant Status (TAS). Malondialdehyde (MDA) as index of lipid peroxidation and C–Reactive Protein (CRP) as a marker of oxidative stress in patients with RA and OA and compared them with healthy control. Method: Serum TAS , MDA and CRP levels were measured in 16 RA and 24 OA patients and compare with those obtained from 25 healthy controls. Results: Serum TAS were significantly lower in RA group than in the OA and control groups (P < 0.05). Serum MDA and CRP levels were significantly higher in patients with RA than in those with OA and healthy subjects (P< 0.05). There were significant negative correlations between TAS and MDA, CRP levels (r = -0.850; p < 0.001) and ( r = -0.498; P < 0.05) respectively and a positive correlation between MDA and CRP levels in the RA group (r = 0.686; P < 0.01). In OA group, the level of CRP was significantly increased (P< 0.05) and there was significant positive correlation between age and MDA level (r = 0.553; P < 0.01). Conclusion: Our results demonstrated that levels of lipid peroxidation are increased in patients with RA compared to controls and patients with OA , In addition serum TAS levels were decreased in RA. Serum TAS levels may be used as a routine and rapid test to verify the levels of oxidative stress in RA. Furthermore correlating TAS and MDA levels with a cute phase reactants such as CRP may give some clues about disease activity in RA .